Effectiveness of Mechanical and Chemical Filter Application on Water Quality, Phytoplankton, and The Emergence of Vibrio Bacteria in Intensive Shrimp Pond - Febriantoro, Indra; Fadjar, Mohammad; Maftuch, Maftuch (International Journal of Marine Engineering Innovation and Research, 2025)
The aquaculture sector plays a crucial role in Indonesia's fisheries industry, especially with the rapid growth of Litopenaeus vannamei shrimp farming. However, intensive aquaculture systems face significant challenges, such as decreased water quality and increased Vibrio bacterial infections, which have the potential to cause diseases with high mortality rates. This study aimed to evaluate the effectiveness of mechanical and chemical filtration systems in improving pond water quality, maintaining phytoplankton balance, and suppressing pathogenic bacterial populations. This study was conducted for 30 days using a randomized group design (RAK) with three treatments, namely ponds without filtration (K), ponds with mechanical filtration (FF), and ponds with chemical filtration (FK). The results showed that chemical filtration was more effective in reducing total organic matter (TOM) and reducing Vibrio density to 1,740-1,880 CFU/mL. Meanwhile, mechanical filtration was more optimal in increasing the phytoplankton population to reach 123,000 ind/m³. The application of the filtration system was also shown to increase dissolved oxygen (DO) levels and reduce total suspended solids (TSS), thus creating more stable water conditions for shrimp. The results of this study indicate that the implementation of an appropriate filtration system can be a strategic solution in supporting the sustainability of the L. vannamei aquaculture industry in Indonesia.